Metabolic acidosis and the progression of chronic kidney disease - Chen, Wei (BMC Nephrol, 2014)
Metabolic acidosis is a common complication of chronic kidney disease. Accumulating evidence identifies acidosis not only as a consequence of, but as a contributor to, kidney disease progression. Several mechanistic pathways have been identified in this regard. The dietary acid load, even in the absence of overt acidosis, may have deleterious effects. Several small trials now suggest that the treatment of acidosis with oral alkali can slow the progression of kidney disease.